Marradi and Language - Montesperelli, Paolo (Italian Sociological Review, 2025)
The methodological reflection made by Alberto Marradi is critical and innovative also thanks to his original attention towards gnoseology. In his two most recent volumes this attention is even more in-depth. According to Marradi, knowledge is the result of the interaction among three crucial “spheres”: referents, thought and language. At least from the “linguistic turn” onwards, language has become a protagonist in many fields of knowledge; but this protagonism is understood in different ways and gives rise to controversies. The first part of this essay concerns the conception of language according to Marradi, with various references to the current debate. The second part illustrates the use of language by Marradi himself, both in his writing methods and in his activity as an educator. This gives rise to a completely original and fundamental teaching in the panorama of social sciences. While the first two are object How The first part of this article illustrates and comments on Marradi’s conception of language. The second part is dedicated to how Marradi himself uses language.